The Effectiveness of Vocabulary Self-Collection Strategy On Students’ Reading And Vocabulary Achievement: A Quasi-Experimental Research - Lazarus Febrisera; Sugirin (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2021)
Reading skill and vocabulary mastery become very pivotal for the ESL students to understand the English language-used properly. That condition should be achieved with the right ways; and one of which is using the VSS. Therefore, this study aims at investigating the effectiveness of Vocabulary Self-collection Strategy (henceforth VSS) on students’ reading and the achievement of vocabulary. The quasi-experimental research was applied and the instruments were pretest-posttest. The VSS was used as the independent variable in this study while reading skill and vocabulary mastery were used as the dependent variables. The pretest-posttest was assigned to gather the data. Then, the test related to reading skill and vocabulary mastery were validated via the expert judgment and a validity of content. Additionally, the instruments regarding its reliability was measured by using the reliability of inter-rater. Afterwards, the parametric statistical technique of T-Test and MANOVA test using SPSS 22. Computer program was employed to analyze the data. The findings showed that VSS reveal a significant effect toward students’ reading skill and vocabulary mastery. This means that the students get easy to understand the English texts given. It is due to their prior knowledge of vocabulary they have too. This study also proves that the use of VSS can be one of the ways of other strategies to teach the reading and vocabulary in the ESL context.